Influence of light intensity on the responses of seedlings of neotropical tree species to nitrogen source - Debiasi, Tatiane V.; Calzavara, Anderson K.; Gomes, Diego G.; Andreas, Izabelle R.; Rondina, Artur B.L.; Duarte, Karoline E.; Pereira, Rodrigo M.; Batista, Bruno L.; Pimenta, José A.; Seabra, Amedea B.; Centeno, Danilo C.; Gaspar, Marília; et al. (Environmental and experimental botany, 2024)
Light intensity plays a crucial role in N uptake and assimilation in plants, but its interaction with different N sources is overlooked. Considering the high energy required for N assimilation, it is hypothesised that low light is critical for the seedling development with both N sources, but with increased light intensity, growing with nitrate (NO3-) becomes favourable in relation to ammonium (NH4+). Seedlings of Cecropia pachystachya (pioneer), Guarea kunthiana (shade-tolerant, understory) and Cariniana estrellensis (shade-tolerant, canopy) were grown in hydroponic medium with NO3- or NH4+ as the sole N source and subjected to low (LL) or high light (HL) for 60 days. All three species showed a decrease in growth when cultivated with NH4+, compared to NO3-, under HL, but not under LL. The decrease in biomass reached 54 % in C. pachystachya, 36 % in G. kunthiana and 26 % in C. estrellensis. Growth reduction was associated with stomatal limitation of photosynthesis and reduced leaf area in C. pachystachya, and with non-stomatal limitation of photosynthesis and oxidative stress in G. kunthiana. Cation uptake was negatively affected by NH4+ in all species. Cariniana estrellensis showed no photosynthetic limitation and showed a higher tolerance to NH4+ under HL in terms of nutrient content. In conclusion, neither N source significantly favors seedling development under LL, while NH4+ is considerably more unfavorable for seedling development than NO3- under HL. •Regardless of the N source, low light limited seedling growth in all three species.•Under high light, NH4+ was considerably unfavorable for seedling development.•Photosynthesis was impaired by NH4+ in two species under high light.•Carbon drain for NH4+ assimilation was a symptom of NH4+ toxicity under high light.•Cation uptake was negatively affected by NH4+ in all species.